2017
DOI: 10.1002/hon.2416
|View full text |Cite
|
Sign up to set email alerts
|

Interphase FISH for BCR‐ABL1 rearrangement on neutrophils: A decisive tool to discriminate a lymphoid blast crisis of chronic myeloid leukemia from a de novo BCR‐ABL1 positive acute lymphoblastic leukemia

Abstract: Discrimination between lymphoid blast crisis of chronic myeloid leukemia (CML) and de novo BCR-ABL1 positive acute lymphoblastic leukemia (ALL) represents a diagnostic challenge because this distinction has a major incidence on the management of patients. Here, we report an uncommon pediatric case of ALL with cryptic ins(22;9)(q11;q34q34) and p190-type BCR-ABL1 transcript. We performed interphase fluorescence in situ hybridization (FISH) for BCR-ABL1 rearrangement on blood neutrophils, which was positive consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(23 reference statements)
0
4
0
1
Order By: Relevance
“…In patients with Ph+ lymphoid blasts, the detection of the BCR-ABL1 rearrangement in granulocytes by the interphase-FISH technique was recently reported as a helpful decisive tool to prove the myeloid origin of the malignant clone and could be used prospectively. 21 The proportion of children (35%) in the present cohort with extramedullary disease seems to be higher than in the adult population. 16,22 This may in part be explained by the higher frequency of lymphoid blast crisis in the present cohort with a propensity of central nervous system disease.…”
Section: Discussionmentioning
confidence: 61%
“…In patients with Ph+ lymphoid blasts, the detection of the BCR-ABL1 rearrangement in granulocytes by the interphase-FISH technique was recently reported as a helpful decisive tool to prove the myeloid origin of the malignant clone and could be used prospectively. 21 The proportion of children (35%) in the present cohort with extramedullary disease seems to be higher than in the adult population. 16,22 This may in part be explained by the higher frequency of lymphoid blast crisis in the present cohort with a propensity of central nervous system disease.…”
Section: Discussionmentioning
confidence: 61%
“…The chromosomal changes that define a transformation to CML-AP include a second Philadelphia chromosome, isochromosome 17q, trisomy 8, trisomy 19, abnormalities of 3q 26.2, or a complex karyotype [ 16 ]. Some studies have shown that B-ALL with BCR-ABL1 is associated with a greater number of additional chromosomal changes when compared with CML in BLP [ 17 ]. Additionally, gains in chromosome 9 are associated with B-ALL with BCR-ABL1, whereas deletions in chromosome 9p are more commonly seen in CML in BLP.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) analysis of sorted cells does not yield reliable results because of the adverse balance between exponential amplification in PCR and the purity of the cell populations sorted from clinical samples. In principle, interphase FISH on neutrophils might expose the BCR::ABL1 rearrangement on cells of myeloid origin after a major blast reduction has occurred-for example, after two weeks of ALL-based induction treatment [32,33]. The limitations of that method are a lack of universal availability of the test or the achievement of a remission that is already too deep to detect the BCR::ABL1 fusion by FISH.…”
Section: Recommendations Diagnosis Of Cml-bp and Patients At Risk For...mentioning
confidence: 99%